Using SoilGrids250m for Overlooking Spatial and Vertical Distribution of Soil Physico-chemical Properties Over Tropical Climate Asia - Munawaroh, Umi; Zaki, Muhamad Khoiru (Research and Social Study Institute, 2025)
Background: Understanding the interaction, spatial and vertical distribution of soil chemical properties over climate type in tropical Asia and various depths of soil is essential for sustainable land management, particularly in regions experiencing dynamic conditions.Aims & Methods: This study investigates the relationships of each parameter such as cation exchange capacity (CEC), soil pH, and soil organic carbon (SOC) tropical Climate Asia. Using stratified random sampling based on Köppen–Geiger climate classifications and a consistent spatial resolution of 0.25° × 0.25°, we analyzed 45 sample points distributed across tropical rainforest, monsoon, and savanna climates. The data were extracted from SoilGrids 250m and reconciled using conservative remapping and bilinear interpolation techniques. Corresponding soil chemical data were obtained from validated regional databases.Result: The results show that a correlation matrix analyzing relationships among key soil physico-chemical properties across multiple depths. Strong positive correlations were found between soil organic carbon (SOC) and total nitrogen (N) (r > 0.8), reflecting their shared origin in organic matter. Bulk density (BD) exhibited moderate to strong negative correlations with SOC and N (r ≈ -0.5 to -0.8), particularly in surface layers, indicating the influence of organic matter on soil structure. Correlations weaken with depth, reflecting reduced nutrient interaction. These patterns highlight the importance of organic matter inputs and minimal soil disturbance in maintaining soil health and guiding sustainable land management strategies.